The Impact of Implementing Guided Inquiry-Based Mathematics E-Worksheets Using the Blended Learning Method on Increasing Students' Critical Thinking - Triyono, Ageng; Kusuma, Arie Purwa; Alghadari, Fiki; Wibowo, Teguh; Marhaeni, Nafida Hetty; Adnan, Mazlini (Indonesian Journal of Mathematics Education, 2024)
The development of mathematics e-worksheets focused on forming critical thinking skills for class VII students is still very minimally carried out by teachers. This research is critical to test the effectiveness of guided inquiry-based e-worksheets implemented using the blended learning method in improving students' critical thinking abilities. The type of research was a quasi-experiment with a nonequivalent pretest-post-test control group design involving two subjects: the experimental group that applied guided inquiry-based e-worksheets and the control group that used other e-worksheets. Each subject group consisted of 18 students from one of the Yogyakarta boarding schools, which became the research population. Research data came from pretest and post-test results collected using critical thinking test instruments developed based on indicators from Facione (2018). Data analysis was conducted using a paired sample t-test followed by an independent sample t-test. The results of data analysis show: (1) there is a significant difference between the pretest and post-test results in the experimental group; (2) there is a significant difference between the results of students' critical thinking tests in the experimental and control groups; and (3) the difference in increasing critical thinking skills of students in the experimental group is higher than students in the control group. These results conclude that applying guided inquiry-based e-worksheets using the blended learning method is more effective than other e-worksheets when viewed from the aspect of increasing students' critical thinking abilities.